A glutamine 'tug-of-war': targets to manipulate glutamine metabolism for cancer immunotherapy. Issue 1 (1st June 2021) - Pallett, Laura J; Dimeloe, Sarah; Sinclair, Linda V; Byrne, Adam J; Schurich, Anna
Summary: Within the tumour microenvironment (TME), there is a cellular 'tug-of-war' for glutamine, the most abundant amino acid in the body. This competition is most evident when considering the balance between a successful anti-tumour immune response and the uncontrolled growth of tumour cells that are addicted to glutamine. The differential effects of manipulating glutamine abundance in individual cell types is an area of intense research and debate. Here, we discuss some of the current strategies in development altering local glutamine availability focusing on inhibition of enzymes involved in the utilisation of glutamine and its uptake by cells in the TME. Further studies are urgently needed to complete our understanding of glutamine metabolism, to provide critical insights into the pathways that represent promising targets and for the development of novel therapeutic strategies for the treatment of advanced or drug resistant cancers.